LEADERSHIP, ORGANIZATIONAL CLIMATE AND EMPLOYEE PERFORMANCE IN SUB-UNIT OF OFFICE OF THE ATTORNEY GENERAL - Ruangwiset, Sorasak; Kayanha, Aroon; Parinyokul, Sukulya (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2023)
The purposes of this research article were to study 1) the level of effect of leadership, which synthesized authentic leadership and inspirational leadership concepts, on employee performance, and 2) the level of effect of organizational climate on employee performance in the sub-unit of the Office of the Attorney General. A quantitative method was applied in this research. The research designs consist of hypothesis testing, correlational studies, cross-sectional descriptive studies, and applied structural equation modeling analysis, and units of analysis are sub-units of the Office of the Attorney General. The results indicated that 1) the leadership had a statistically significant effect on employee performance, and 2) the organizational climate had a statistically significant effect on employee performance. The results showed that the Office of the Attorney General should enhance and develop leadership, organizational climate, and employee performance.